2009
DOI: 10.1080/17439880903338606
|View full text |Cite
|
Sign up to set email alerts
|

Marginalised behaviour: digital annotations, spatial encoding and the implications for reading comprehension

Abstract: Within large scale educational assessment agencies in the UK, there has been a shift towards assessors marking digitally scanned copies rather than the original paper scripts that were traditionally used. This project uses extended essay examination scripts to consider whether the mode in which an essay is read potentially influences the judgements made about it, employing qualitative and quantitative data-gathering approaches to focus on the annotation practices of readers who are assessing extended essays, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
0
14
1
2
Order By: Relevance
“…However, they were more effective in understanding the texts when reading from paper. In another study assessing recall, Johnson and N adas (2009) showed that participants had poorer recall on screen, with more difficulty remembering the location of details in the texts. W€ astlund, Reinikka, Norlander, and Archer (2005) conducted two experiments comparing students' reading from paper versus computer, to measure written production and comprehension.…”
Section: Introductionmentioning
confidence: 96%
“…However, they were more effective in understanding the texts when reading from paper. In another study assessing recall, Johnson and N adas (2009) showed that participants had poorer recall on screen, with more difficulty remembering the location of details in the texts. W€ astlund, Reinikka, Norlander, and Archer (2005) conducted two experiments comparing students' reading from paper versus computer, to measure written production and comprehension.…”
Section: Introductionmentioning
confidence: 96%
“…The readers annotate to focus on what they are interested in and to reduce the workload by place marking. This type of annotation is seen in other studies [15,17] but the importance of navigation in code comprehension makes it more critical for code understanding. Digital ink annotation in IDEs could be a valuable aid to support code navigation.…”
Section: Discussionmentioning
confidence: 68%
“…Offloading information to paper reduces the amount of cognitive workload the reader needs to perform [15]. P08 mentioned that one of his challenges was trying to remember everything.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations